Ecology of scleractinian corals in the waters of Port Dickson and their tolerance to sedimentation - Lee, Yoke Lee (2005)
This study was conducted in two parts, field data collection and laboratory experiments. Coral reef surveys were done using Line Intercept Transect and Random Sampling Method while an 8-month sedimentation rate monitoring programme was conducted along the coast of Port Dickson at Batu 7, 8, 9 and Tanjung Tuan using sediment traps. Laboratory experiments were conducted on 12 specimens of Porites lutea and Favites abdita respectively using the Buoyant Weighing Technique to monitor coral growth rates during Suspended Sediment Experiments (SSEs). The corals were also subjected to burial experiments to estimate their sediment tolerance and sediment rejection abilities. The sedimentation rates in Port Dickson and Tanjung Tuan were high, ranging from 59.61 ± 17.57 mg cm-2 day-1 to 220.61 ± 145.52 mg cm-2 day-1. Sediment type was predominantly silt and clay fractions. X-ray diffraction analysis indicated that these fine sediments were transported into the coastal environment through rivers. Percentage clay ranged between 18.72 ± 4.45 % and 33.81 ± 7.19 %; silt between 12.28 ± 9.95 % and 41.17 ± 4.46 %; sand between 29.1 ± 5.31 % and 46.83 ± 8.94 %; and organic matter between 1.81 ± 1.64 % and 19.14 ± 16.03 %. Coral reef surveys conducted on the reef flat of Tanjung Tuan have found Porites spp. to be the most abundant coral type with a percentage cover of 42.57 %; followed by Goniastrea spp. at 20.87 %; Favites spp. at 9.81% and Favia spp. at 7.84 %. Overall live coral cover for all four stations was poor; ranging from 11.7 % to 16.8 %. Dead coral cover was between 4 % and 20.25 % while macroalgae cover was very high; ranging from 27.3 % to 57.3 %. Results from SSE 1 and 2 show that there was no significant difference in the mean growth rates between the treatment and control groups for both Favites abdita and Porites lutea. In BE 1, Favites abdita specimens survived burial better than Porites lutea specimens because they were able to manipulate and reject particles of sand from their surfaces. However, all specimens in the treatment group for both species were unable to survive BE 2.